How air pollution influences the difference between overweight and obesity: a comprehensive analysis of direct and indirect correlations - Yu, Muchun; Xie, Jinchen; Liu, Yanyan (Frontiers in Public Health, 2024)
Background: Obesity, conceptualized as excessive or abnormal fat accumulation, is a major risk to public health. Air pollution is an important potential obesogenic determinant, while the clear direct and indirect correlation between air pollution and obesity remains vague. This study aims to capture the comprehensive scenario between air pollution and obesity by causally identifying the direct and indirect correlation correlations.We used national-representative data from the China Family Panel Survey. Air pollution concentration Conclusions: Air pollution in general posed positive influences on overweight/obesity, where PM2.5 and PM10 posed positive influences and SO2 and CO were negative. Meanwhile, the influence was more significant in males, aged individuals, and rural groups compared to their female, young, and urban counterparts. Additionally, social behavior predominantly mediated the potential mechanism between air pollution and obesity.